2003
DOI: 10.1016/s1525-0016(03)00002-9
|View full text |Cite
|
Sign up to set email alerts
|

Transduced CD34+ cells from adrenoleukodystrophy patients with HIV-derived vector mediate long-term engraftment of NOD/SCID mice

Abstract: X-linked adrenoleukodystrophy (ALD), an inherited demyelinating disorder of the central nervous system, can be corrected by allogeneic bone marrow transplantation, likely due to the turnover of brain macrophages that are bone marrow derived. ALD is characterized by an accumulation of very long chain fatty acids (VLCFA) due to the deficiency of an ATP binding cassette transporter that imports these fatty acids in peroxisomes. Murine retroviral transduction results in metabolic correction of ALD CD34(+) cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…CD34 ϩ cells were isolated from UCB of normal individuals or from granulocyte colonystimulating factor MPB from ALD patients after obtaining their informed consent and in accordance with approved institutional guidelines. CD34 ϩ cells were purified by immunomagnetic selection (17). Fluorescence-activated cell sorting (FACS) analysis performed on a FACStar (Becton Dickinson) showed that the CD34 ؉ population had a purity of over 90%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD34 ϩ cells were isolated from UCB of normal individuals or from granulocyte colonystimulating factor MPB from ALD patients after obtaining their informed consent and in accordance with approved institutional guidelines. CD34 ϩ cells were purified by immunomagnetic selection (17). Fluorescence-activated cell sorting (FACS) analysis performed on a FACStar (Becton Dickinson) showed that the CD34 ؉ population had a purity of over 90%.…”
Section: Methodsmentioning
confidence: 99%
“…Human UCB and MPB CD34 ϩ cells were transduced according to previously described procedures (17,18) with a self-inactivating lentiviral͞HIV vector (TRIP⌬U3) carrying expression cassettes for the human ALD protein or the enhanced GFP (EGFP) under the control of the elongation factor 1␣ promoter. Briefly, CD34 ϩ cells were incubated with lentiviral vector in the presence of four recombinant human cytokines (stem cell factor, Flt3-ligand, IL-3, pegylatedmegakaryocyte growth and differentiation factor; UCB ϭ 100͞ 10͞100͞60 ng͞ml, MPB ϭ all 10 ng͞ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical efficacy of lovastatin therapy in X-ALD patients remains to be proven. of ALD protein in monocytes/macrophages derived from engrafted stem cells [126]. Additionally, it was shown that cells derived from human CD34+ cells isolated from cord blood or peripheral blood migrate into the brain after infusion into immunodeficient mice and differentiate into perivascular and ramified microglia.…”
Section: Five-year Viewmentioning
confidence: 99%
“…After laying the preclinical groundwork for efficient ex vivo lentiviral vector-mediated transduction of human hematopoietic stem cells with wild type ABCD1, a French group described the initial human experience with this gene-therapy approach. [65][66][67][68] Two boys with ALD, both aged 7 years, lacked HLA-matched donors or UCB units for allogeneic HCT. Both demonstrated progressive cerebral disease on MRI.…”
Section: Autologous Genetically Modified Hematopoietic Cell Transplamentioning
confidence: 99%